Silicon nitride substrate
By ensuring uniform solid-solution oxygen and thermal conductivity ratios in silicon nitride substrates, the challenges of quality stability and cold-heat cycle resistance are addressed, resulting in high-quality, uniformly performing individual pieces.
Patent Information
- Application Number
- JP2023144253
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
Existing silicon nitride substrates face challenges in achieving high uniformity, leading to variations in quality stability among individual pieces, especially in resistance to cold and heat cycles.
A silicon nitride substrate with uniform solid-solution oxygen and thermal conductivity across its central and edge regions, achieved by maintaining specific ratios (Oe/Oc and Te/Tc) within the range of 0.95 to 1.05, ensuring consistent properties and improved manufacturing efficiency.
The substrate enables the production of individual pieces with high quality stability and enhanced resistance to cold and heat cycles, facilitating efficient manufacturing with consistent performance.
Smart Images

Figure 2025037364000001
Abstract
Description
[Technical field]
[0001] The present invention relates to silicon nitride substrates. [Background technology]
[0002] Silicon nitride sintered bodies have excellent mechanical strength, thermal conductivity, and electrical insulation, and are therefore used as circuit boards by bonding a metal circuit plate to the surface. For example, Patent Document 1 discloses a silicon nitride substrate that contains silicon nitride and magnesium, and in which the ratio of the amount of magnesium at the intersection of diagonal lines on the surface to the average amount of magnesium at four points located 3 mm inward from a corner of the surface toward the intersection of diagonal lines is 0.80 to 1.00. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] WO2020 / 203787 issue Summary of the Invention [Problem to be solved by the invention]
[0004] In the case of silicon nitride substrates, from the viewpoint of manufacturing efficiency, a method is sometimes used in which a large silicon nitride substrate is manufactured and then cut into a number of individual pieces. In this case, if there is variation in quality in the silicon nitride substrate before cutting, there will be variation in quality among the individual pieces obtained by cutting, so in order to obtain individual pieces with high quality stability, it is necessary for the silicon nitride substrate to have high uniformity.
[0005] In particular, silicon nitride substrates are used in locations where heat dissipation performance is important, taking advantage of their high thermal conductivity, and it is important that they do not peel off from metal circuit plates even when subjected to repeated thermal cycles. As in Patent Document 1, studies have been conducted to improve the uniformity of the magnesium content of silicon nitride substrates from the perspective of warping, but studies have not been conducted sufficiently from the perspective of thermal cycle resistance. The present invention has been made in view of these circumstances, and aims to obtain a highly uniform silicon nitride substrate from which individual pieces with high quality stability in thermal cycle resistance can be obtained. [Means for solving the problem]
[0006] In order to solve the above problems, the present inventors have conducted extensive research and have found that in order to obtain individual pieces with high quality stability in terms of thermal cycle resistance, it is important for a silicon nitride substrate to have uniformity in both the amount of dissolved oxygen, which is a factor that affects the state of silicon nitride particles, and the thermal conductivity, which reflects the characteristics of the sintered body structure, and thus have completed the present invention.
[0007] That is, the present invention provides a silicon nitride substrate having a ratio Oe / Oc of the amount of dissolved oxygen in the central portion Oc to the amount of dissolved oxygen in the edges Oe of 0.95 to 1.05, and a ratio Te / Tc of the thermal conductivity Tc of the central portion to the thermal conductivity Te of the edges Te of 0.95 to 1.05. It is preferable that the amount of dissolved oxygen in the central portion Oc is 0.05% or less, and the thermal conductivity Tc of the central portion is 90 W / m K or more. Furthermore, it is preferable that the silicon nitride substrate of the present invention has a main surface having a size of 140 mm × 140 mm or more. Effect of the Invention
[0008] The silicon nitride substrate of the present invention makes it possible to obtain individual pieces having high quality stability from the viewpoint of thermal cycles. This makes it easy to efficiently manufacture individual pieces having excellent quality stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In the silicon nitride substrate of the present invention, the ratio Oe / Oc of the amount of dissolved oxygen in the center Oc to the amount of dissolved oxygen in the edges Oe is within the range of 0.95 to 1.05, and the ratio Te / Tc of the thermal conductivity Tc of the center to the thermal conductivity Te of the edges is within the range of 0.95 to 1.05. This means that the amount of dissolved oxygen and the thermal conductivity are uniform between the center and the edges of the silicon nitride substrate.
[0010] In the present invention, the central portion means the vicinity of the intersection of two diagonals drawn from the four corners of the main surface of the silicon nitride substrate. Specifically, to measure the thermal conductivity Tc of the central portion, a test piece cut to a size of 25 mm x 25 mm centered on the intersection of the diagonals is used. The amount of dissolved oxygen in the central portion Oc is measured by taking a test piece for measuring the thermal conductivity of the central portion, and then taking a required amount of samples from around the test piece.
[0011] In the present invention, the end means the vicinity of the four corners of the main surface. Specifically, for the measurement of the thermal conductivity Te of the end, a test piece cut to a size of 25 mm x 25 mm is used, centered on a point 50 mm diagonally from the corner of the main surface. The measurement of the dissolved oxygen amount Oe of the end is performed by taking a test piece for measuring the thermal conductivity of the end, and then taking a necessary amount of samples from around the test piece. The dissolved oxygen amount Oe of the end is measured at all four points, and the point with the largest difference from Oc, that is, the point with the value of Oe / Oc farthest from 1.00 among the four points, is adopted. Similarly, the thermal conductivity Te of the end is measured at all four points, and the point with the largest difference from Tc and the value of Te / Tc farthest from 1.00 is adopted.
[0012] The amount of dissolved oxygen in the present invention can be measured by an inert gas fusion-infrared absorption method using an oxygen / nitrogen analyzer, and means the amount of oxygen dissolved in the crystals of silicon nitride particles of the substrate. Specifically, the measurement is performed by crushing a silicon nitride substrate, removing the auxiliary phase by acid treatment, sealing 25 mg of the sample in a tin capsule and introducing it into a graphite crucible, heating it at 5.5 kW for 20 seconds, degassing the adsorbed gas, heating it at 0.8 kW for 10 seconds, and then increasing the temperature from 0.8 kW to 4 kW over 350 seconds, measuring the amount of carbon dioxide generated during that time, and converting it into the oxygen content to obtain the total oxygen amount. During the 350-second temperature increase, the oxygen generated early is oxygen derived from oxides present on the surface of silicon nitride particles (external oxygen), and the oxygen generated later corresponds to dissolved oxygen (internal oxygen) that is dissolved in the silicon nitride crystals, so a perpendicular line is drawn from the part corresponding to the valley of these two measurement peaks, from which the background measured in advance is subtracted, to separate the two peaks. The amount of dissolved oxygen (internal oxygen) and the amount of external oxygen are calculated by proportionally allocating the areas of the respective peaks. In addition to the two peaks, small peaks due to impurities or the measurement environment may be detected, but these small peaks are ignored and the two largest peaks are used in calculating the amount of dissolved oxygen. The part corresponding to the valley between the two measurement peaks is the point between the two measurement peaks where the amount of oxygen is the smallest.
[0013] The silicon nitride substrate of the present invention has a ratio Te / Tc of the thermal conductivity Tc of the center to the thermal conductivity Te of the edge in the range of 0.95 to 1.05, which means that the thermal conductivity is uniform between the center and the edge of the silicon nitride substrate.
[0014] In the present invention, the thermal conductivity is measured by the laser flash method. Specifically, the surface of the test piece is blasted, then coated with gold and carbon, and the measurement can be performed using a laser flash method thermal constant measurement device. The thermal conductivity is calculated by multiplying the thermal diffusivity, density, and specific heat. The specific heat of the silicon nitride substrate is set to 0.68 (J / g K), and the density is measured using an automatic hydrometer.
[0015] Although it is not clear why a silicon nitride substrate having high quality stability in thermal cycle resistance can be obtained by setting Oe / Oc in the range of 0.95-1.05 and Te / Tc in the range of 0.95-1.05, the present inventors believe as follows. That is, the amount of dissolved oxygen affects the state of silicon nitride particles, and it is presumed that if the amount of dissolved oxygen differs for each piece obtained by cutting the silicon nitride substrate, the state of silicon nitride particles differs for each piece, which affects the behavior of expansion and contraction during thermal cycles. One of the main causes of peeling between the metal circuit board during thermal cycles is the generation of stress due to the difference in expansion and contraction between silicon nitride and metal during thermal cycles, so the difference in the amount of dissolved oxygen between the pieces leads to a difference in thermal cycle resistance. Furthermore, if the thermal conductivity of each individual piece obtained by cutting the silicon nitride substrate differs, the way heat is transferred during a thermal cycle will differ for each individual piece. As a result, there will be differences in the expansion and contraction behavior of the individual pieces during a thermal cycle, and the difference in thermal conductivity between the individual pieces will lead to differences in resistance to thermal cycles.
[0016] Generally, silicon nitride substrates are most likely to show differences in characteristics between the center and the edge due to differences in the sintering environment, so if the characteristics are uniform between the center and the edge, it can be said that the substrate is uniform overall. Therefore, silicon nitride substrates with Oe / Oc in the range of 0.95 to 1.05 and Te / Tc in the range of 0.95 to 1.05 have the same amount of dissolved oxygen and thermal conductivity, and as a result, they all have the same thermal cycle resistance. It is presumed that this makes it possible to obtain silicon nitride substrates with high quality stability in terms of thermal cycle resistance. The silicon nitride substrate of the present invention preferably has an Oe / Oc ratio within the range of 0.97 to 1.03, and more preferably 0.99 to 1.01. The silicon nitride substrate of the present invention preferably has a Te / Tc ratio within the range of 0.97 to 1.03, and more preferably 0.99 to 1.01.
[0017] The dissolved oxygen in the silicon nitride substrate of the present invention is preferably 0.055% or less, more preferably 0.050% or less. By setting Oc within the above range, the silicon nitride substrate can have high thermal conductivity, and the heat dissipation at high temperatures can be improved, enabling an extended life in thermal cycles. Similarly, Oe is preferably 0.055% or less, more preferably 0.050% or less.
[0018] The silicon nitride substrate of the present invention preferably has a Tc of 90 W / m·K or more, and more preferably 100 W / m·K or more. With Tc in the above range, heat dissipation at high temperatures can be improved, enabling an extended life for thermal cycles. Similarly, Te is preferably 90 W / m·K or more, and more preferably 100 W / m·K or more. There are no particular upper limits for Tc and Te, but they are usually 150 W / m·K or less.
[0019] The silicon nitride substrate of the present invention is preferably plate-shaped. The size of the main surface is preferably 140 mm x 140 mm or more. When the size of the main surface is large, the number of pieces obtained by cutting it increases, thereby improving manufacturing efficiency, but generally, the difference in environment between the center and the end parts during firing becomes large, making it difficult to improve quality stability, and therefore the effect of the present invention is large. The upper limit of the size of the main surface is not particularly limited, but is generally 200 mm x 200 mm or less. The ratio of the length of the long side to the short side of the main surface is not particularly limited. The thickness of the silicon nitride substrate of the present invention is not particularly limited, but is generally 0.1 mm to 2.0 mm.
[0020] The silicon nitride substrate of the present invention can be obtained, for example, by mixing silicon nitride powder, a sintering aid, and water for 20 hours or more, adding a binder and mixing for 20 hours or more to obtain a raw material slurry, and then molding the slurry to obtain a green body, which is then fired.
[0021] The reason why the silicon nitride substrate of the present invention can be obtained by the above-mentioned manufacturing method is not clear, but the present inventors consider it as follows. In a general manufacturing process of a silicon nitride substrate, the surface of the silicon nitride powder is gradually oxidized during the processes of mixing raw materials, molding, firing, etc. If the surface of the silicon nitride powder is oxidized to form an oxide film, it may cause an increase in dissolved oxygen or a disturbance in the crystal structure of silicon nitride after sintering, resulting in a decrease in thermal conductivity. However, since it is difficult to control the oxidation reaction during the substrate manufacturing process, there are areas where oxidation is relatively advanced and areas where oxidation is relatively suppressed, and it has been difficult to obtain a silicon nitride substrate with extremely high uniformity in dissolved oxygen amount and thermal conductivity. Here, as described above, by mixing the silicon nitride powder, sintering aid, and water in a ball mill for 20 hours or more, and then adding a binder and mixing in a water-containing state for 20 hours or more, the oxidation of the surface of the silicon nitride powder is promoted by the action of water, and a sufficient oxide film is formed on almost the entire surface of the silicon nitride powder in the green body. In particular, the binder is essential for forming silicon nitride powder, and in the present invention, it is particularly important to add the binder and perform mixing for 20 hours or more. The mixing after adding the binder can prevent the silicon nitride powder from being crushed by mitigating the impact of the binder. If the silicon nitride powder is crushed, new surfaces will be generated and the oxidation state of the surface of the silicon nitride powder will vary, but by adding the binder and mixing for 20 hours or more in a state where crushing is prevented, the surface of the silicon nitride powder can be sufficiently oxidized to achieve uniform oxidation. Once a sufficient oxide film is formed on the surface of the silicon nitride powder, no further oxidation reaction will occur, and it is presumed that the progress of the oxidation reaction in the subsequent steps will be uniform within the silicon nitride substrate, and a silicon nitride substrate with extremely high uniformity in the amount of dissolved oxygen and thermal conductivity can be obtained.
[0022] The time for mixing the silicon nitride powder, sintering aid, and water in a ball mill before adding the binder is not particularly limited as long as it is 20 hours or more, but since a long mixing time reduces production efficiency, it is preferably 50 hours or less, particularly 30 hours or less. The mixing time after adding the binder is also not particularly limited as long as it is 20 hours or more, but since a long mixing time reduces production efficiency, it is preferably 50 hours or less, particularly 30 hours or less.
[0023] The rotation speed of the ball mill during ball mill mixing is 10 rpm to 50 rpm, and preferably 20 rpm to 30 rpm, which allows sufficient oxidation while preventing the silicon nitride powder from being excessively pulverized, which would reduce the uniformity of the surface oxidation state.
[0024] The silicon nitride powder may be made of α-type silicon nitride, β-type silicon nitride, or a mixture of these, but it is preferable to include β-type silicon nitride because β-powder is less likely to undergo grain growth during sintering than α-powder and is easier to control uniformity. The β-phase ratio of the silicon nitride powder is preferably 80% or more, more preferably 90% or more, and more preferably 99% or more. The β-phase ratio of the silicon nitride powder means the peak intensity ratio of the β-phase to the total of the α-phase and β-phase in the silicon nitride powder [100 x (peak intensity of β-phase) / (peak intensity of α-phase + peak intensity of β-phase)], and is determined by powder X-ray diffraction (XRD) measurement using CuKα rays. More specifically, it is determined by calculating the weight ratio of the α-phase and β-phase in the silicon nitride powder according to the method described in C.P. Gazzara and D.R. Messier: Ceram. Bull., 56 (1977), 777-780.
[0025] The particle size of the silicon nitride powder is not particularly limited, but the average particle size D50 is preferably 0.4 to 1.2 μm, and more preferably 0.6 to 1.0 μm. The average particle size D50 can be measured with a laser diffraction / scattering particle size distribution measuring device. The specific surface area of the silicon nitride powder is preferably 12 to 30 m. 2 / g, and 18 to 24m 2 In the present invention, the specific surface area refers to a BET specific surface area measured by a BET single point method using nitrogen gas adsorption.
[0026] The sintering aid can be any known sintering aid without any particular limitation, and examples thereof include oxides such as yttria, magnesia, ceria, and calcia, carbonitride compounds, and nitride compounds that do not contain oxygen. Examples of carbonitride compounds include Y2Si4N6C, Yb2Si4N6C, Ce2Si4N6C, and MgSi4N6C. Examples of nitride compounds include MgSiN2. These sintering aids may be used alone or in combination of two or more. The amount of the sintering aid is not particularly limited, but is preferably 5 to 20 parts by mass, and more preferably 7 to 10 parts by mass, relative to 100 parts by mass of silicon nitride powder.
[0027] The amount of water is not particularly limited, but from the viewpoint of thoroughly mixing and forming a sufficient oxide film on the surface of the silicon nitride powder, it is preferable to use an amount that results in a solids concentration in the slurry (slurry concentration) of 50 to 70 mass %.
[0028] The binder may be any known binder without any particular limitation, and examples thereof include polyvinyl alcohol, polyvinyl acetal, polyvinyl pyrrolidone, acrylic resin, polyacrylamide, urethane resin, polyester, polyether, melamine, epoxy resin, cellulose resin, and starch. These binders may be used alone or in combination of two or more. The content of the binder is preferably 1 to 30 parts by mass relative to 100 parts by mass of the silicon nitride powder.
[0029] The raw material slurry may contain other components in addition to the silicon nitride powder, sintering aid, binder, and water. Examples of other components include dispersants, plasticizers, and antifoaming agents. The other components may be added before the binder is added, when the binder is added, or at any time after the binder is added. For example, the dispersant is used to enhance the dispersibility of the silicon nitride powder and the sintering aid powder in the slurry, and generally, a surfactant can be suitably used. The surfactant may be any known one, and may be used without any restrictions. Specific examples of surfactants that can be suitably used in the present invention include carboxylated trioxyethylene tridecyl ether, diglycerol monooleate, diglycerol monostearate, carboxylated heptaoxyethylene tridecyl ether, tetraglycerol monooleate, hexaglycerol monooleate, sorbitan laurate, sorbitan oleate, sorbitan trioleate, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, and the like. These surfactants may be used alone or in combination of two or more. The amount of the dispersant can be appropriately selected, and can be selected, for example, from the range of 0.1 to 5 parts by mass per 100 parts by mass of the total amount of the silicon nitride powder and the sintering aid powder. Within this range, the upper limit of the amount of dispersant is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1 part by mass or less.
[0030] The raw material slurry can be molded into a desired shape to obtain a green body. A doctor blade method can be used as a molding method for easily obtaining a plate-like green body from the raw material slurry.
[0031] Since the green body contains water, it is preferable to dry it before firing in order to remove the water. The drying conditions are not particularly limited, but the green body may be dried by heating it to about 30°C to 150°C.
[0032] In addition, since the green body contains organic components such as binders, dispersants, plasticizers, and antifoamers, degreasing may be performed after drying and before firing to remove the organic components in order to facilitate firing. The degreasing conditions are not particularly limited, but may be performed, for example, by heating the green body to 450 to 650°C in air or in an inert atmosphere such as nitrogen or argon.
[0033] The green body is fired to obtain a silicon nitride substrate. The firing conditions are not particularly limited, but the firing temperature is preferably 1700°C to 2000°C, and more preferably 1800°C to 1950°C, and the firing time is preferably 1 to 30 hours, and more preferably 3 to 20 hours. The firing pressure may be normal pressure or may be increased pressure.
[0034] The silicon nitride substrate of the present invention can be cut into a plurality of pieces. Since the silicon nitride substrate of the present invention has high uniformity in dissolved oxygen content and thermal conductivity, when cut into a plurality of pieces, it is easy to obtain pieces having the same thermal cycle characteristics, and it can be said to have excellent quality stability. In other words, by using the silicon nitride substrate of the present invention, pieces having excellent quality stability can be efficiently manufactured.
[0035] The method for cutting the silicon nitride substrate is not particularly limited, and can be performed by a method such as a slicer, a laser scriber, etc. The number of pieces obtained by cutting one silicon nitride substrate is not particularly limited, but it is preferable to cut into six or more pieces, particularly in a form in which the central portion and the end portions are different pieces, and more preferably nine or more pieces. EXAMPLES
[0036] In the following, examples are described in order to specifically explain the present invention, but the present invention is not limited to these examples. The measurements of the various items in the examples and comparative examples were performed by the following methods.
[0037] (1) Amount of dissolved oxygen in silicon nitride substrate The amount of dissolved oxygen in silicon nitride powder was measured by inert gas fusion-infrared absorption method using an oxygen / nitrogen analyzer (HORIBA: EMGA-920). As a sample, 25 mg of a measurement sample was obtained from the silicon nitride substrate obtained in each Example and Comparative Example. The measurement sample was enclosed in a tin capsule (a tin capsule manufactured by LECO was used for the tin capsule) and introduced into a graphite crucible, heated at 5.5 kW for 20 seconds, and after degassing of the adsorbed gas, heated at 0.8 kW for 10 seconds, and heated from 0.8 kW to 4 kW over 350 seconds, the amount of carbon dioxide generated during that time was measured and converted into oxygen content. During the 350-second temperature rise, the oxygen generated at the beginning is oxygen (external oxygen) derived from the oxide present on the surface of the silicon nitride particles, and the oxygen generated later corresponds to the dissolved oxygen (internal oxygen) that is dissolved in the silicon nitride crystal. Therefore, a perpendicular line was drawn from the part corresponding to the valley of these two measurement peaks, from which the background measured in advance was subtracted, to separate the two peaks. The amount of dissolved oxygen (internal oxygen) and the amount of external oxygen were calculated by proportionally allocating the areas of the respective peaks.
[0038] (2) Thermal conductivity of silicon nitride substrate The silicon nitride substrates obtained in each of the Examples and Comparative Examples were cut out to obtain test pieces with a main surface of 25 mm x 25 mm. The surfaces of the test pieces were blasted, then coated with Au and carbon, and measurements were performed using a laser flash thermal constant measurement device (TC-9000, manufactured by Advance Riko Co., Ltd.). Thermal conductivity was calculated by multiplying thermal diffusivity, density, and specific heat. The specific heat of the silicon nitride substrate was set to 0.68 (J / g K), and density was measured using an automatic hydrometer (DMA-220H, manufactured by Shinko Denshi Co., Ltd.).
[0039] (3) Thermal cycle resistance The silicon nitride substrate was cut into 40 mm x 10 mm to obtain 20 silicon nitride samples for evaluation. A copper plate was bonded to the evaluation sample by the AMB (Active Metal Brazing) method to prepare a metallized substrate. In the AMB method, a brazing material (Ag-Cu-Ti 75:21:4 (mass ratio)) containing an active metal was screen-printed on both sides of the silicon nitride sample, a copper plate of 0.3 mm thickness was placed, and heated at 850 ° C for 20 minutes in a vacuum. Then, a pattern was formed by immersion etching in an aqueous ferric chloride solution to obtain a predetermined shape. Furthermore, in order to remove the remaining composite material, the copper plate portion was eroded in an acidic ammonium fluoride aqueous solution, and then washed with water to prepare a metallized sample. Next, a heat cycle test (3000 times at -40 to 200 ° C) was performed on the metallized sample, and visual evaluation was performed according to the following criteria. ○: No cracks or peeling were observed in any of the metallized samples. ×: Cracks and peeling were observed in some metallized samples. If this evaluation is rated as good, then all of the individual pieces obtained by cutting the large silicon nitride substrate have consistently high thermal cycle resistance, and the individual pieces obtained have high quality stability in terms of thermal cycle resistance, making it possible to say that the silicon nitride substrate is highly uniform.
[0040] The silicon nitride substrate was manufactured using the following raw materials containing silicon nitride powder and a sintering aid. <Silicon nitride powder> ·Betaization rate: 99% ·Average particle size D50: 0.9μm <Sintering aid> - Yttria (manufactured by Shin-Etsu Chemical Co., Ltd.) Magnesia (manufactured by Ube Material Industries, Ltd.) <Binders and dispersants> Binder resin: Acrylic resin (manufactured by Fujikura Kasei Co., Ltd.) Dispersant: Cerna D735 (manufactured by Chukyo Yushi Co., Ltd.)
[0041] <Example 1> 100 parts by mass of silicon nitride powder, 5 parts by mass of yttria, 3 parts by mass of magnesia, and 0.5 parts by mass of dispersant were weighed, and mixed in a ball mill at 25 rpm for 24 hours using water as a solvent and a resin pot and silicon nitride balls. Water was weighed in advance so that the concentration of the slurry was 60% by mass, and was poured into the resin pot. Then, 22 parts by mass of binder was added, and mixing was further performed at 25 rpm for 24 hours. Next, defoaming and viscosity adjustment were performed using a vacuum defoamer (manufactured by Sayama Riken Co., Ltd.) to prepare a raw material slurry. Then, using the raw material slurry, sheet molding was performed by the doctor blade method, and the solvent was evaporated by drying at 100°C in air, and a green body (green sheet) with a width of 750 mm and a thickness of 420 μm was obtained. The green sheet obtained as described above was cut to a size of 200 mm x 268 mm for the main surface, and then degreased in dry air at 550°C. The degreased green sheet was then placed in a sintering vessel and sintered at 1880°C for 9 hours in a nitrogen atmosphere under a pressure of 0.9 MPa·G to obtain a silicon nitride substrate with a main surface of 150 mm x 200 mm. The evaluation results are shown in Table 1.
[0042] <Example 2> 100 parts by mass of silicon nitride powder, 5 parts by mass of yttria, 3 parts by mass of magnesia, and 0.5 parts by mass of dispersant were weighed, and mixed in a ball mill at 25 rpm for 20 hours using water as a solvent and a resin pot and silicon nitride balls. Water was weighed in advance so that the concentration of the slurry was 60% by mass, and was poured into the resin pot. Then, 22 parts by mass of binder was added, and mixing was further performed at 25 rpm for 24 hours. Next, defoaming and viscosity adjustment were performed using a vacuum defoamer (manufactured by Sayama Riken Co., Ltd.) to prepare a raw material slurry. Then, using the raw material slurry, sheet molding was performed by the doctor blade method, and the solvent was evaporated by drying at 100°C in air, and a green body (green sheet) with a width of 750 mm and a thickness of 420 μm was obtained. The green sheet obtained as described above was cut to a size of 200 mm x 268 mm for the main surface, which was then degreased in dry air at 550°C, after which the degreased green sheet was placed in a sintering vessel and sintered at 1880°C for 9 hours in a nitrogen atmosphere under a pressure of 0.9 MPa·G to obtain a silicon nitride substrate with a main surface of 150 x 200 mm. The evaluation results are shown in Table 1.
[0043] <Comparative Example 1> 100 parts by mass of silicon nitride powder, 5 parts by mass of yttria, 3 parts by mass of magnesia, and 0.5 parts by mass of dispersant were weighed, and mixed in a ball mill at 25 rpm for 24 hours using water as a solvent and a resin pot and silicon nitride balls. Water was weighed in advance so that the concentration of the slurry was 60% by mass, and was poured into the resin pot. Then, 22 parts by mass of binder was added, and mixing was further performed at 25 rpm for 12 hours. Next, defoaming and viscosity adjustment were performed using a vacuum defoamer (manufactured by Sayama Riken Co., Ltd.) to prepare a raw material slurry. Then, using the raw material slurry, sheet molding was performed by the doctor blade method, and the solvent was evaporated by drying at 100°C in air, and a green body (green sheet) with a width of 750 mm and a thickness of 420 μm was obtained. The green sheet obtained as described above was cut to a size of 200 mm x 268 mm for the main surface, and then degreased in dry air at 550°C. The degreased green sheet was then placed in a sintering vessel and sintered at 1880°C for 9 hours in a nitrogen atmosphere under a pressure of 0.9 MPa·G to obtain a silicon nitride substrate with a main surface of 150 mm x 200 mm. The evaluation results are shown in Table 1.
[0044] [Table 1]
Claims
1. A silicon nitride substrate, in which the ratio Oe / Oc of the amount of dissolved oxygen Oc in the center to the amount of dissolved oxygen Oe in the edges is 0.95 to 1.05, and the ratio Te / Tc of the thermal conductivity Tc of the center to the thermal conductivity Te of the edges is 0.95 to 1.
05.
2. 2. The silicon nitride substrate in accordance with claim 1, wherein said central portion has a dissolved oxygen content Oc of 0.05% or less and a thermal conductivity Tc of 90 W / m·K or more.
3. 2. The silicon nitride substrate in accordance with claim 1, wherein the size of the main surface is 140 mm x 140 mm or more.
Citation Information
Patent Citations
Silicon nitride substrate, silicon nitride-metal complex, silicon nitride circuit board, and semiconductor package
WO2020203787A1